(untitled) (Journal of the College of Basic Education, 2022)
The difficult meaning of many unfamiliar and new words is‘motivated’ by their original and semantic meaning. In an EFL context, thisoffers the possibility of presenting a number of difficult words in ways thatpromote insightful learning rather than blind memorization. Associating aword with its semantic change and etymology has been shown to enhancecomprehending and then remembering. This effect seems in accordancewith dual coding theory, as the etymological association is likely to call upa mental image of a concrete scene which can be stored in memoryalongside the verbal form. The present study explores the possibility oftaking this technique beyond mere mnemonics. A series of tests that are setup with the participation of students who study English in their higherstudy are reported. The results show that knowledge of the origin andsemantic changes of these new and unfamiliar words can effectively helplearners comprehend their meaning and then ease their retention. Not onlydoes the task of knowing word meaning on the basis of etymologicalinformation appear practical, it seems to facilitate recall, too. Finally, theresults suggest that knowledge of the origin of unfamiliar words can helplearners estimate whether they might have more than one meaning. Failing to remember previously encountered words is one of thecommonly reported complaints of EFL learners. Among the variety ofcommonly used vocabulary reinforcing techniques, making students awareof etymological accounts of words is a relatively under researched area inthe literature. The present study, therefore, aims at exploring the effect ofpresenting etymological accounts of 20 unfamiliar words on short- andlong-term vocabulary retention of EFL learners. The participants (20) aremembers of two higher studies classes randomly assigned to experimentaland control groups. While both groups are asked to look up the meaning ofthe words in their dictionaries, the participants in the experimental groupreceived a short instruction on the etymologies of the words. The results of